Vagaries of desire : a collection of philosophical essays - Airaksinen, Timo (Value inquiry book series. Philosophy, literature, and politics, ISSN 0929-8436, 2019)
Vagaries of Desire is a major collection of new essays by Timo Airaksinen on the philosophy of desire. The first part develops a novel account of the philosophical theory of desire, including Girard. The second part discusses Kafka's main works, namely The Castle, The Trial, and Amerika, and Thomas Hobbes and the problems of intentionality. The text develops such linguistic tropes as metaphor and metonymy in connection with topics like death and then applies them to Kafka's texts. The third part makes an effort to understand the mysteries of sadism and masochism in philosophical and rhetorical terms. The last article criticizes Thomas Nagel's influential account of sexual perversion and develops a viable alternative.
Keywords: Hobbes, Thomas; Kafka, Franz, : 1883-1924; Desire (Philosophy); halu; filosofia; seksuaalinen käyttäytyminen; etiikka; tunteet; himo; seksuaaliset poikkeavuudet; sadomasokismi; kirjallisuudentutkimus; yhteiskuntafilosofia; teoriat